Sustainable Development of Mangrove Ecosystem Policy in South Sulawesi from the Perspectives of Siyāsah and Fiqh al-Bi’ah - Hamzah Hamzah; Irfan Amir; Sultan Hasanuddin; Tarmizi Tarmizi; Muhammad Fazlurrahman Syarif (JURIS (Jurnal Ilmiah Syariah), 2023)
This research aims to examine the policy of sustainable mangrove ecosystem development in South Sulawesi from the perspective of siyāsah and fiqh al-bi’ah. The questions raised are how the construction and implications of the policy of sustainable mangrove ecosystem development are, and how the reformulation of the concepts of siyāsah and fiqh al-bi’ah affects the policy that has been set. The data in this research are primary data from interviews, observations, and documentation, as well as secondary data from relevant literature. Data collection methods were carried out through interviews, observations, and documentation to be analyzed descriptively qualitatively based on the approach of siyāsah and fiqh al-bi’ah. The results of the research show that the policy of sustainable mangrove ecosystem utilization is realized through the establishment of regulations related to mangrove management at both the national and regional levels. The policy is implemented through the formation of the Regional Mangrove Working Group (KKMD) of South Sulawesi as a group that works to preserve the mangrove ecosystem. The policies implemented have implications for legal aspects, aspects of the economy based on ecotourism, environmental sustainability, education, and religious social. The policy that has been set is in line with the concept of siyāsah dusturiyah and fiqh al-bi’ah based on maslahah. The perspective of siyāsah dusturiyah and fiqh al-bi’ah plays a role in strengthening and supporting government policies in the effort to preserve the sustainable mangrove ecosystem.